Impactos da institucionalização na saúde mental do idoso - Dantas, Luã Carlos Valle [UNESP]; Ferreira, Luiz Augusto Knalfec; Andrade, Carmen Valéria dos Santos; Silva, Sandra Maria Souza e; Soares, Edvaldo [UNESP] (My University, 2013)
The present work proposes an analysis of the conditions of the elderly on a Brazilian context, focusing the institutionalized elders and the nuances of the institutionalization process on their mental health. Bibliographical analysis and participative observation were used as method. On the discussion, the present work demonstrates that the institutionalization have harmful effects to the elders, at their mental health and from this, proposes a multidisciplinary view of the process.

Este trabalho propõe analisar a situação do idoso no contexto brasileiro, enfocando os idosos institucionalizados e as nuances do processo de institucionalização na saúde mental dos mesmos. Utilizou como metodologia a análise bibliográfica e observação participativa. Na discussão, o trabalho demonstra que a institucionalização tem efeitos danosos para o idoso em sua saúde mental, e a partir disto propõe uma perspectiva multidisciplinar do processo.
Impacts of Institutionalization Process on Elders Mental Health
Keywords: Institucionalização; Saúde Mental; Idoso; Psicologia